An Analysis upon Creation and Mysticism in the Poetry of Rabindranath Tagore: A Case Study of Gitanjali: Exploring the Nature Mysticism in Rabindranath Tagore's Gitanjali (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mysticism categorically lacks an authority and anything and everything that is related to God is put under the term mysticism. This research paper focuses Gitanjali which is classified under mystic poetry. The endeavor here is to look for the mystical elements in the poem and how it qualifies to be a mystical poetry. An analysis of words and ideas reveals that it is the love for nature and God that made Tagore enter the realm of mysticism. However, his mystical experiences are quite different from those of the experiences of enlightened saints of India. Saints’ mysticism is a result of the union achieved through deep meditation, but in Tagore’s case it is only love and desire for the union. As a result of this, his Gitanjali can be considered as Nature Mysticism rather than Soul or God Mysticism only which enlightened saints and poets like Kalidasa or Auribindo can achieve.Tagore, rising high above mere propagandist philosophizing about religious tenets and ritualism, feels the presence of the divine in every object of his creation and is inextricably tangled in it. His tryst with the divine will not take place in some transcendental world on some other plane; his is the tryst with God…takes place on this very earth and his songs of Gitanjali give expression to his ecstatic pleasure that he has already experienced.